High-performance ferroelectric-dielectric multilayered thin films for energy storage capacitors - Silva, José Pedro Basto (2019)
Herein, the effect of the insertion of a thin dielectric HfO2:Al2O3 (HAO) layer at different positions in the Pt/0.5Ba(Zr0.2Ti0.8)O3–0.5(Ba0.7Ca0.3)TiO3 (BCZT)/Au structure on the energy storage performance of the capacitors is investigated. A high storage performance is achieved through the insertion of a HAO layer between BCZT and Au layers. The insertion of the dielectric layer causes a depolarization field which results in a high linearity hysteresis loop with low energy dissipation. The Pt/BCZT/HAO/ Au capacitors show an impressive energy storage density of 99.8 J cm−3 and efficiency of 71.0%, at an applied electric field of 750 kV cm−1. Further, no significant change in the energy storage properties is observed after passing 108 switching cycles through the capacitor. The presence of resistive switching (RS) in leakage current characteristics confirms the strong charge coupling between ferroelectric and insulator layers. The same trend of the RS ratio and the energy storage performance with the variation of the architecture of the devices suggests that the energy storage properties can be improved through the charge coupling between the layers. By combining ferroelectrics and dielectrics into one single structure, the proposed strategy provides an efficient way for developing highly efficient energy storage capacitors.